Mary as an inspiration for the empowerment of Southern African christian women disproportionately infected/affected by HIV/AIDS - Chigumira, Godfrey (University of Birmingham, 2012)
The thesis proposes a liberative Mariological model for southern African Christian women disproportionately infected/affected by HIV/AIDS. The first chapter argues that women are disproportionately infected and affected by HIV and AIDS impacts in southern Africa. It proposes the utilisation of Mary, the mother of Jesus, as an inspirational symbol for the empowerment of southern African Christian women against HIV/AIDS. The second chapter explains the basic themes of the thesis of ‘symbol’, ‘inspiration’ and ‘empowerment’ in relation to Mary. It also illustrates how Mary is utilised as a symbol of empowerment within the chapters that follow. Chapter three considers some African theological writings on Mary, mainly by African women theologians and also reflects on how Mary interacts with some communities in southern Africa. Chapters four to eight are built on chapter themes of Mary as mother, as mother of sorrows, Mary’s incarnational role, Mary as virgin, and as a revolutionary respectively. Within each chapter theme, the thesis considers how Mary could inspire southern African Christian women for empowerment against HIV infection and AIDS impacts. In chapter nine, a Marian healing ritual for women living with HIV/AIDS is proposed, using feminist ritual healing guidelines, for the women’s empowerment, followed by the concluding chapter.
Free